Analisis Sentimen Ulasan Pengguna Aplikasi Adakami Di Google Playstore Menggunakan Naive Bayes - Pangestu, Faisal; Irwansyah (The Indonesian Journal of Computer Science, 2024)
The AdaKami application is an online loan platform that attempts to give millions of people in Indonesia high-quality financial access without the need for collateral. Ten million downloads of the Adakami app have been made through the Google Playstore. The issue in this study is how well the Adakami application reviews are classified using the Naive Bayes method, specifically how many of the reviews have positive or negative values. How to use the Naive Bayes method for the Adakami application review is the goal of this study. The knowledge of the accuracy of the Naive Bayes approach in examining Google Playstore evaluations is the advantage of this research. The investigation produced a classification assessment of the naive Bayes algorithm in Google evaluations of the Adakami application.